Development of Communication Skills for Students in Early Childhood Education by Using Problems - Based Learning - Tanapron, Tawan; Chiwakumnuan, Phatcharee (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
This research the objectives are to 1. develop communication skills of first year students majoring in early childhood education and 2. to compare communication skills of first year students majoring in early childhood education by using problems-based method before and after the communication skills development activities and problem-based communication with role-playing activities, storytelling, essay writing and read the essay Samples Used in this research were 28 freshman year students majoring in Early Childhood Education, Faculty of Education, Thepsatri Rajabhat University in the second semester of the academic year 2021. The instruments used in this research consisted of 10 learning management plans, and 16 checklist communication skills assessment forms. The statistics used were mean and standard deviation. and t-test. The results showed that 1. students majoring early childhood education who received a problem-based communication skill development elicited higher scores and 2. a comparison of the difference in communication skills scores before and after the treatment demonstrated that students majoring in early childhood education had listening, speaking, reading, and writing skills with statistically significantly higher scores than before the activity.